From the Gut to the Liver: Another Organ to Watch in FAP Patients. (24th March 2016) - Paulson, Spencer; Patel, Charmi; Patel, Hitendra
Abstract : We report a rare association of hepatocellular carcinoma with familial adenomatous polyposis in a young patient and its clinical significance. A 28-year-old female with a past medical history of familial adenomatous polyposis (FAP) and subsequent colonic adenocarcinoma underwent total colectomy. She later presented with intermittent right upper quadrant pain and nausea of four months' duration. MRI of the abdomen revealed multiple liver lesions, the largest 8.5 cm in diameter, with radiologic features suggestive of hepatocellular carcinoma. A CT-guided liver biopsy demonstrated well-differentiated HCC which was confirmed by immunohistochemistry. In patients with a history of FAP, a heightened awareness of the possibility of concurrent or subsequent HCC is warranted.